2006
DOI: 10.1111/j.1523-5378.2006.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Amoxicillin–Metronidazole Plus Famotidine or Lansoprazole for Amoxicillin–Clarithromycin–Proton Pump Inhibitor Treatment Failures for Helicobacter pylori Infection

Abstract: Famotidine treatment including metronidazole-amoxicillin as second-line therapy provided a high eradication rate similar to lansoprazole therapy. Famotidine is therefore expected to serve as a useful H. pylori eradication regimen in patients with proton pump inhibitor allergy, an economic benefit in terms of reduced health-care costs is also anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…Adicionalmente, en este país se compararon las tasas de erradicación de la triple terapia estándar con metronidazol frente a la triple terapia con famotidina, y la terapia cuádruple con bismuto o concomitante por 7 días de duración, obteniendo la triple terapia estándar con metronidazol tasas de erradicación por ITT del 97% versus la triple terapia con famotidina del 94%, y en análisis por ITT/PP para la terapia triple estándar con metronidazol del 88.5-93.9%, versus la terapia cuádruple sin bismuto o concomitante del 82.7-84.3% 34,35 . En España, la terapia cuádruple con bismuto versus la triple terapia con rifabutina de 7 días de duración logró porcentajes de erradicación por ITT para cada terapia del 70.4 y del 44.4% 36 .…”
Section: Ensayos Clínicos Aleatorizadosunclassified
“…Adicionalmente, en este país se compararon las tasas de erradicación de la triple terapia estándar con metronidazol frente a la triple terapia con famotidina, y la terapia cuádruple con bismuto o concomitante por 7 días de duración, obteniendo la triple terapia estándar con metronidazol tasas de erradicación por ITT del 97% versus la triple terapia con famotidina del 94%, y en análisis por ITT/PP para la terapia triple estándar con metronidazol del 88.5-93.9%, versus la terapia cuádruple sin bismuto o concomitante del 82.7-84.3% 34,35 . En España, la terapia cuádruple con bismuto versus la triple terapia con rifabutina de 7 días de duración logró porcentajes de erradicación por ITT para cada terapia del 70.4 y del 44.4% 36 .…”
Section: Ensayos Clínicos Aleatorizadosunclassified
“…After failure of a combination of PPI, amoxicillin and clarithromycin, a theoretically correct alternative would be the use, as second option, of other PPI-based triple therapy including amoxicillin (that does not induce resistance) and metronidazole (an antibiotic not used in the first trial), and several authors have reported encouraging results with this strategy [Ueki et al 2009;Murakami et al 2008Murakami et al , 2006Shirai et al 2007;Matsuhisa et al 2006;Nagahara et al 2004;Shimoyama et al 2004;Isomoto et al 2003;Miwa et al 2003]. However, in our experience, when this therapy has been administered twicedaily for 1 week, eradication rates lower than 50% have been obtained [Gisbert et al 1999a]; the subsequently use of higher (three times per day) antibiotic doses, was followed only by a mild increase in eradication rate (58%), which was still unacceptable [Gisbert et al 1999a].…”
Section: Introductionmentioning
confidence: 99%
“…The antibiotic resistance of H. pylori is considered to be a signifi cant factor in determining the success of eradication. 16,22 In particular, recent evidence has stressed the major infl uence of clarithromycin resistance on the outcome of therapy including clarithromycin. The cure rate may drop as much as 55% because of the presence of clarithromycin-resistant H. pylori strains.…”
Section: Discussionmentioning
confidence: 99%